IMPLEMENTASI BUSINESS INTELLIGENCE MENGGUNAKAN TABLEAU UNTUK VISUALISASI PREDIKSI KELULUSAN MAHASISWA - Santhi, Trihana; Sari, Aprilia Monica; Putra, Dewa Ketut Alit Maha; Mahendra, Gede Surya; Ariasih, Made Putri (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
Prediction of student graduation plays an important role in college programs to help students stay high-achieving and graduate on time, as well as produce the best graduates. Information about the number of students graduating in college plays a significant role in decision-making through visual representation of data. This article aims to describe data on student graduation predictions in college through visual representation using Business Intelligence and Tableau tools with data from www.kaggle.com. The results of this research are presented in the form of a dashboard that includes GPA, academic achievement, organizational involvement, and gender in college, which can be used to support decision-making. Visualizing data through analysis using an interactive Tableau dashboard is expected to make information more engaging and easily understandable. Predicted students who graduate on time have adequate GPA, participate in campus activities, and are mostly male.